Analisis Tinggi Seawall Optimal sebagai Proteksi Pantai terhadap Overtopping di Pantai Kota Maba - Rizal Tukuwain; Hanie Teki Tjendani; Sajiyo Sajiyo (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2026)
Maba City Beach is a coastal area that is vulnerable to abrasion and sea wave runoff (overtopping) due to the influence of waves and tides. This study aims to analyze the optimal seawall height as coastal protection against overtopping at Maba City Beach, East Halmahera Regency. The research method used is a quantitative approach through coastal hydrodynamic analysis based on wind, fetch, wave, bathymetry, topography, and tidal data. The analysis was carried out through the stages of calculating wave transformation, refraction and shoaling coefficients, breaking waves, wave setup, and wave run-up to determine the planned seawall elevation. The results showed that the dominant wind direction came from the East and Northeast with an effective fetch of 60.691 km. The deep sea wave height was obtained at 1.7 m with a wave period of 5.7 seconds. Wave transformation produced a wave height near the coast of 1.77 m with a wave energy of 3.97 J/m² and an energy flux of 13.62 W/m. The breaking wave occurred at a depth of 1.95 m with a breaking wave height of 1.66 m and a spilling breaker type. The tidal analysis results showed a Highest High Water Level (HHWL) value of 2.09 m. The calculation of wave setup of 0.25 m and run-up of 0.15 m resulted in an optimal seawall elevation of 2.99 m above Mean Sea Level (MSL). This elevation is considered capable of reducing the risk of overtopping and providing effective protection to the coastal area of ​​Maba City Beach.